Trust in Countries’ Institutions and Subjective Well-being: Data from 21 Countries - Vadvilavičius, Tadas (Psichologija, 2024)
In psychological research, greater attention is paid to the closest social systems of a person and their importance for that person’s well-being. However, it cannot be ruled out that the state-level social system and its assessment can also be significant predictors of a person’s subjective well-being. The purpose of this study is to determine the impact of an individual’s trust in parliament, political parties, the political and legal system, and the police on life satisfaction and subjective happiness. Data from the European Social Survey Round 10, which includes 21 countries (n = 34079), were used for the analysis. The results revealed that the people have the most trust in the police and the least trust in political parties. Additionally, the results show that men trust parliament and the legal system more than women and are more satisfied with life. Structural equation modeling revealed that trust in the state predicts higher life satisfaction and subjective well-being. The results revealed that the state, as the highest social system, is also significant for a person’s subjective well-being. The results also showed differences between countries. The obtained research findings open up possibilities for further research.
Keywords: trust in government; trust in legal system; life satisfaction; subjective happiness; European social survey